1993
DOI: 10.1089/hum.1993.4.3-249
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Safety of Intrasplenic Hepatocyte Transplantation: Relevance toEx VivoGene Therapy and Liver Repopulation in Acute Hepatic Failure

Abstract: Hepatocytes transplanted into the host liver engraft promptly, retain normal function, and survive indefinitely. Although intrasplenic transplantation is effective in delivering hepatocytes to the liver, to define potentially limiting complications, we studied its safety in normal, cirrhotic, and partial portal vein-ligated rats. In normal rats, portal pressures increased severalfold after hepatocyte transplantation but returned to normal within 3 weeks. In contrast, in portal hypertensive rats with partial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 31 publications
3
56
0
2
Order By: Relevance
“…1 These diseases are attractive targets for hepatocyte transplantation or gene transfer into hepatocytes. Hepatocyte transplantation has been performed in animal models [2][3][4] as well as limited human clinical trials, 5,6 but only Ͻ1% of the hepatocyte mass could be replaced. This has resulted in poor clinical efficacy of the procedure.…”
Section: Recent Work Has Convincingly Demonstrated That Adult Bone Mamentioning
confidence: 99%
“…1 These diseases are attractive targets for hepatocyte transplantation or gene transfer into hepatocytes. Hepatocyte transplantation has been performed in animal models [2][3][4] as well as limited human clinical trials, 5,6 but only Ͻ1% of the hepatocyte mass could be replaced. This has resulted in poor clinical efficacy of the procedure.…”
Section: Recent Work Has Convincingly Demonstrated That Adult Bone Mamentioning
confidence: 99%
“…Previous studies showed that severe portal hypertension develops during cell injection into the spleen, although after several weeks portal pressures, as well as angiographic appearances of the portal circulations, were normal in recipients. 14 To document the kinetics of this change in portal pressures, we transplanted 2 ϫ 10 7 or 7.5 ϫ 10 7 hepatocytes in groups of three rats each. Interestingly, portal pressures were normal in all animals after 1, 3, 7, and 10 days of cell transplantation.…”
Section: Hemodynamic Consequences Of Cell Translocations and Entry Intomentioning
confidence: 99%
“…We further analyzed the process by which portal hypertension induced by intrasplenic cell transplantation is resolved. 14 The hypothesis was that, on translocation of transplanted cells from the hepatic sinusoids and integrations in liver plates, changes in the portal vascular bed will resolve as the hepatic circulation is restored. Finally, we investigated whether specific factors, such as the vascular endothelial growth factor (VEGF), which is also known as vascular permeability factor (VPF), was released during cell engraftment.…”
mentioning
confidence: 99%
“…10,11 functional support of chronic hepatic failure and congenital It has been reported that a PH of 70% stimulated DNA metabolic disorders, the long-term survival of a large number synthesis of intrasplenically transplanted hepatocytes, but no of transplanted hepatocytes in ectopic sites or the liver of increase in the number of surviving hepatocytes was found. 15,16 The stimulative effect of a PH of 70% might be rapidly utilized by the remnant liver and did not affect the proliferation of intrasplenically transplanted hepatocytes.…”
Section: Discussionmentioning
confidence: 99%